(untitled) (American Journal of Business Management, Economics and Banking, 2025)
Concise summary of the article’s content and key findings. This comprehensive article provides a detailed analysis of the financial risks associated with public-private partnerships (PPPs). The annotation offers a concise yet informative summary of the study’s key findings, highlighting the critical challenges and considerations that decision-makers must navigate when engaging in these collaborative ventures. The article examines a range of financial risks, including cost overruns, revenue shortfalls, and debt financing issues, drawing on case studies and empirical data to illustrate the complexities involved. The annotation sets the stage for the in-depth exploration of the topic, introducing the reader to the methodological approach, the analysis of results, and the practical implications for practitioners working in the field of PPP project development and management.